The Coordination Between B Cell Receptor Signaling and the Actin Cytoskeleton During B Cell Activation - Li, Jingwen; Yin, Wei; Jing, Yukai; Kang, Danqing; Yang, Lu; Cheng, Jiali; Yu, Ze; Peng, Zican; Li, Xingbo; Wen, Yue; Sun, Xizi; Ren, Boxu; et al. (Frontiers in Immunology, 2019)
B-cell activation plays an important role in the immune system and is initiated via interaction between the B cell receptor (BCR) and specific antigens. In recent years with the help of modern imaging techniques, it was found that the cortical actin cytoskeleton changes dramatically during B-cell activation. In this review, we discuss how actin-cytoskeleton reorganization regulates BCR signaling in different stages of B-cell activation, specifically in response to antigen stimulation, and also how this reorganization is mediated by BCR signaling molecules. Abnormal BCR signaling is involved in the progression of lymphoma and immunological diseases including autoimmune disorders, and recent studies have proved that impaired actin cytoskeleton can devastate the normal activation of B cells. Therefore, to figure out the coordination between the actin cytoskeleton and BCR signaling may reveal an underlying mechanism of B-cell activation, which has potential for new treatments for B-cell associated diseases.